Pyocin S2 (Sa) kills Pseudomonas aeruginosa strains via the FpvA type I ferripyoverdine receptor36780 - Sarah Denayer; Cornelis,P. (J.Bacteriol., 2007)
Soluble (S-type) pyocins are Pseudomonas aeruginosa bacteriocins that kill nonimmune P. aeruginosa strains via a specific receptor. The genes coding for pyocin Sa (consisting of a killing protein and an immunity protein) were cloned and expressed in Escherichia coli. Sequence analysis revealed that Sa is identical to pyocin S2. Seventy-nine strains of P. aeruginosa were tested for their sensitivity to pyocins S1, S2, and S3, and their ferripyoverdine receptors were typed by multiplex PCR. No strain was found to be sensitive to both S2 and S3, suggesting that the receptors for these two pyocins cannot coexist in one strain. As expected, all S3-sensitive strains had the type II ferripyoverdine receptor fpvA gene, confirming our previous reports. S1 killed strains irrespective of the type of ferripyoverdine receptor they produced. All S2-sensitive strains had the type I fpvA gene, and the inactivation of type I fpvA in an S2-sensitive strain conferred resistance to the S2 pyocin. Accordingly, complementation with type I fpvA in trans restored sensitivity to S2. Some S2-resistant type I fpvA-positive strains were detected, the majority (all but five) of which had the S1-S2 immunity gene. Comparison of type I fpvA sequences from immunity gene-negative S2-sensitive and S2-resistant strains revealed only a valine-to-isoleucine substitution at position 46 of type I FpvA. However, both type I fpvA genes conferred the capacity for type I pyoverdine utilization and sensitivity to S2. When these two type I fpvA genes were introduced into strain 7NSK2 carrying mutations in type II fpvA (encoding the type II pyoverdine receptor) and fpvB (encoding the alternative type I receptor), growth in the presence of type I pyoverdine was observed and the strain became sensitive to S2. We also found that type I pyoverdine could signal type II pyoverdine production via the type I FpvA receptor in 7NSK2
Keywords: 0; a; ALL; alternative; an; analysi; analysis; article; AS; at; Bacterial Outer Membrane Proteins; Bacterial Proteins; Bacteriocins; Belgium; Brussels; CODING; Comparison; drug effects; Escherichia coli; gene; Gene Expression Regulation,Bacterial; Genes; Genetic Complementation Test; genetics; growth; i; im; inactivation; interaction; interactions; IS; journal; Laboratories; Membrane Proteins; metabolism; Molecular; multiplex PCR; Mutation; observed; p; PCR; polymerase chain reaction; Print; production; protein; Proteins; Pseudomonas; Pseudomonas aeruginosa; Pyocins; Receptor; receptors; report; reports; Research; Research Support; resistance; SB - IM; SENSITIVITY; Sequence Analysis; specific; strain; toxicity; Type; utilization